Lubiprostone Decreases the Small Bowel Transit Time by Capsule Endoscopy: An Exploratory, Randomised, Double-Blind, Placebo-Controlled 3-Way Crossover Study - Matsuura, Mizue (Gastroenterol Res Pract, 2014)
The aim of this study was to investigate the usefulness of lubiprostone for bowel preparation and as a propulsive agent in small bowel endoscopy. Six healthy male volunteers participated in this randomized, 3-way crossover study. The subjects received a 24 μg tablet of lubiprostone 60 minutes prior to the capsule ingestion for capsule endoscopy (CE) and a placebo tablet 30 minutes before the capsule ingestion (L-P regimen), a placebo tablet 60 minutes prior to CE and a 24 μg tablet of lubiprostone 30 minutes prior to CE (P-L regimen), or a placebo tablet 60 minutes prior to r CE and a placebo tablet again 30 minutes prior to CE (P-P regimen). The quality of the capsule endoscopic images and the amount of water in the small bowel were assessed on 5-point scale. The median SBTT was 178.5 (117–407) minutes in the P-P regimen, 122.5 (27–282) minutes in the L-P regimen, and 110.5 (11–331) minutes in the P-L regimen (P = 0.042). This study showed that the use of lubiprostone significantly decreased the SBTT. We also confirmed that lubiprostone was effective for inducing water secretion into the small bowel during CE.